The roles of mutated SPINK1 gene in prostate cancer cells. (16th September 2022) - Pan, Xiuyi; Tan, Junya; Yin, Xiaoxue; Liu, Qianqi; Zheng, Linmao; Su, Zhengzheng; Zhou, Qiao; Chen, Ni
Abstract: SPINK1-positive prostate cancer (PCa) has been identified as an aggressive PCa subtype. However, there is a lack of definite studies to elucidate the underlying mechanism of the loss of SPINK1 expression in most PCa cells except 22Rv1 cells, which are derived from a human prostatic carcinoma xenograft, CWR22R. The aim of this study was to investigate the mechanisms of SPINK1 protein positive/negative expression and its biological roles in PCa cell lines. SPINK1 mRNA was highly expressed in 22Rv1 cells compared with LNCaP, C4-2B, DU145, and PC-3 cells, and the protein was only detected in 22Rv1 cells. Among these cell lines, the wild-type SPINK1 coding sequence was only found in 22Rv1 cells, and two mutation sites, the c.194G>A missense mutation and the c.210T>C synonymous mutation, were found in other cell lines. Our further research showed that the mutations were associated with a reduction in SPINK1 mRNA and protein levels. Functional experiments indicated that SPINK1 promoted PC-3 cell proliferation, migration, and invasion, while knockdown of SPINK1 attenuated 22Rv1 cell proliferation, migration, and invasion. The wild-type SPINK1 gene can promote the malignant behaviors of cells more than the mutated ones. Cell cycle analysis by flow cytometry showed that SPINK1 decreased the percentage of cells in the G0 /G1 phase and increased the percentage of S phase cells. We demonstrated that the c.194G>A and c.210T>C mutations in the SPINK1 gene decreased the mRNA and protein levels. The wild-type SPINK1 gene is related to aggressive biological behaviors of PCa cells and may be a potential therapeutic target for PCa.